Dental Health Status and Knowledge Improvement After Dental Health Empowerment at Elementary School Student in Gresik, East Java - Nugraha, Alexander Patera; Alida, Alida; Rahmawati, Dwi (Indonesian Journal of Dental Medicine, 2022)
Background: Dental caries is the most common dental and oral health condition. Children's growth and development may be hampered by dental cavities. Furthermore, it may raise the risk of stunting owing to a lack of dietary intake, which may have an impact on quality of life. Oral and dental health empowerment is required to increase dental health knowledge and understanding of dental disorders, particularly during the corona virus disease-19 (COVID-19) pandemic. Objective: to describe oral and dental health knowledge improved following dental health empowerment at Madrasah Ibtidaiyah Miftahul Ulum Elementary School in Melirang, Bungah Distric, Gresik City, East Java. Material and Methods: Three surveyors were responsible for data collecting. This study's sample size was 150 people ranging from fourth to sixth grade. The seminar covered dental and oral health and was provided via teledentistry. The participants were asked to fill out a Google form for the pre- and post-test to determine the improvement of oral and dental health knowledge for the dental health empowerment evaluation. Result: The majority of oral and dental health participants understood the presentation on oral and dental health empowerment. The post-test percentage was higher (93.59%) than the pre-test rate (56.81%). Conclusion: The program findings demonstrated that oral and dental health empowerment via teledentistry was an effective medium for increasing elementary school children's understanding of dental and oral health status.